Hegel's lectures on the history of philosophy - Hegel, Georg Wilhelm Friedrich (Humanities paperback library, 1996)
Based on the "Geschichte der Philosophie" this edition has continued to interest scholars due to the insight it affords into Hegel's view of the history of philosophy, for an understanding of his own theory, and in itself, as the first philosophical history of philosophy.